EVALUASI PROGRAM PENDIDIKAN KARAKTER BERBASIS BUDAYA SEKOLAH (STUDI KASUS DI SMP NEGERI 8 AMBON) - Adha Marche Lino Untajana; Sally Edoxiana Untajana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study evaluates the implementation of character education at SMP Negeri 8 Ambon, Indonesia, using the Goal-Free Evaluation model to identify actual outcomes beyond predefined objectives. Character education, integrated into daily school culture as